Relationship and sexual quality in the wake of COVID-19: Effects of individual regulatory focus and shared concerns over the pandemic - Rodrigues, D. L.; Balzarini, R. N. (European Journal of Investigation in Health, Psychology and Education, 2023)
Research has shown mixed findings regarding the effect of the COVID-19 pandemic on relation-ship and sexual quality and activity. We argue that some of these findings might be understood considering people’s predisposition to maintain safety (i.e., prevention focus) or take risks (i.e., promotion focus), and sharing concerns with one’s partner about the pandemic. A longitudinal study (N = 153) tested if regulatory focus before the pandemic (November 2019) was associated with relationship quality, sexual quality, and joint sexual activity later on (June 2020) and whether these effects were moderated by shared concerns over the pandemic. Results showed that participants more focused on prevention experienced higher relationship quality later on, but also less sexual quality and less frequent joint sexual activity, when they shared fewer (vs. more) con-cerns with their partner. In contrast, participants more focused on promotion experienced higher relationship quality later on when they shared more (vs. less) concerns with their partner. These results indicate how individuals’ regulatory focus and shared concerns in times of crisis, such as the COVID-19 pandemic, can have downstream consequences on people’s relational and sexual dynamics. We offer insights for mental health professionals to improve psychosocial health and well-being when people are faced with critical events.